1995
DOI: 10.1063/1.115084
|View full text |Cite
|
Sign up to set email alerts
|

Auger electron spectroscopy study of silver incorporation in epitaxial Y–Ba–Cu–O superconducting films grown on MgO by laser ablation

Abstract: We have studied by Auger electron spectroscopy the incorporation of silver in epitaxial YBa2Cu3O7 (YBCO) thin films fabricated by pulsed laser deposition using YBCO+Ag 10% targets. Films were grown on MgO substrates. The silver was found in a thin layer, of approximately 50 nm in depth. X-ray photoelectron spectroscopy confirmed that the Ag is in its metallic form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…Thick polycrystalline films of YBa 2 Cu 3 O 7−x (1 2 3) doped with silver were produced by the standard screen printing ceramic method starting with YBCO samples with silver added in 10 wt.%, according to the reported procedure elsewhere [14]. The YBCO/Ag thick films were grown on (1 0 0) MgO substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Thick polycrystalline films of YBa 2 Cu 3 O 7−x (1 2 3) doped with silver were produced by the standard screen printing ceramic method starting with YBCO samples with silver added in 10 wt.%, according to the reported procedure elsewhere [14]. The YBCO/Ag thick films were grown on (1 0 0) MgO substrates.…”
Section: Methodsmentioning
confidence: 99%
“…This kind of effect ͑dif- ference in the amount of silver in the targets and films despite using optimized deposition conditions͒ has been observed in case of other materials. 19 Nevertheless, we believe that most of the silver leaves the film-site after playing its role in improving the oxygenation of BST films and residual silver possibly prevents the unpinning of domain walls. Both of these effects are manifested in the improved electrical properties of BST films.…”
mentioning
confidence: 93%
“…8,13 Even though, the use of Ag improves the microstructure and other properties, the presence of metallic Ag can be detrimental depending on the application. Hence, it is desirable that the final film be free from Ag.…”
Section: 9mentioning
confidence: 99%
“…2,9 Amid the improvement in microstructure and other physical properties in these films, the final film always contained some amount of Ag. 2,7,9,[12][13][14] Also, it has been found that Ag stays in the metallic form. 7,8,13 This would be undesirable in some cases where the presence of metallic Ag can be detrimental to certain characteristics like high-frequency loss in superconducting films or dielectric loss in dielectric films.…”
mentioning
confidence: 99%
See 1 more Smart Citation